Antioxidative Capacity of Liver- and Adipose-Derived Mesenchymal Stem Cell-Conditioned Media and Their Applicability in Treatment of Type 2 Diabetic Rats. (3rd February 2021) - Elshemy, Mohamed M.; Asem, Medhat; Allemailem, Khaled S.; Uto, Koichiro; Ebara, Mitsuhiro; Nabil, Ahmed
Abstract : Type 2 diabetes mellitus (T2DM) is mainly characterized by insulin resistance and impaired insulin secretion, which cannot be reversed with existing therapeutic strategies. Using mesenchymal stem cells (MSCs), cell-based therapy has been demonstrated in displaying therapeutic effects in T2DM for their self-renewable, differentiation potential, and immunosuppressive properties and higher levels of angiogenic factors. Stem cell therapies are complicated and have a serious adverse effect including tumor formation and immunogenicity, while using mesenchymal stem cell-conditioned media (MSC-CM) significantly reduces stem cell risk, maintaining efficacy and showing significantly higher levels of growth factors, cytokines, and angiogenic factors that stimulate angiogenesis and promote fracture healing in diabetes. In the present study, we investigated the therapeutic potential of the liver and adipose MSC-CM in diabetic endothelial dysfunction compared with standard insulin therapy. Fifty adult male Sprague Dawley rats were divided equally into 5 groups as follows: control, diabetic, diabetic+insulin, diabetic+liver MSC-CM, and diabetic+adipose MSC-CM; all treatments continued for 4 weeks. Finally, we observed that liver MSC-CM therapy had the most apparent improvement in levels of blood glucose; HbA1c; AGEs; lipid panel (cholesterol, TG, LDL, HDL, and total lipids); renal function (urea, uric acid, creatinine, and total protein); liver function (AST, ALT, ALP, bilirubin, and albumin); CPK; C-peptide; HO-1; inflammatory markers including IL-6, TNF- α, and CRP; growth factors (liver and serum IGF-1); amylase; histopathological changes; pancreatic cell oxidative stress; and antioxidant markers (MDA, GSH, ROS, CAT, SOD, HO-1, and XO) toward the normal levels compared with insulin and adipose MSCs-CM. Moreover, both the liver and adipose MSC-CM relieved the hyperglycemic status by improving pancreatic islet β cell regeneration, promoting the conversion of alpha cells to beta cells, reducing insulin resistance, and protecting pancreatic tissues against oxidative stress-induced injury as well as possessing the ability to modulate immunity and angiogenesis. These results indicated that MSC-CM infusion has therapeutic effects in T2DM rats and may be a promising novel therapeutic target.